2016
DOI: 10.1190/geo2015-0230.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of a Ag-Au-rich epithermal system in British Columbia, Canada, using airborne z-axis tipper electromagnetic and ground-based magnetotelluric data

Abstract: We have evaluated results from a study combining airborne z-axis tipper electromagnetic (ZTEM) and ground-based magnetotelluric (MT) data to image an epithermal system in British Columbia. The spatially coincident use of these two methods allowed for a direct comparison of both data sets in the overlapping frequency band and showed that both measurements were consistent. Inversion of just the ZTEM data suffered from the lack of electric field amplitude information, which could be provided by the MT data. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…5). The agreement is similar to that reported by Hübert et al (2016) at the Newton deposit. The two datasets can also be displayed as induction arrows as in Fig.…”
Section: G E O L O G Y a N D P R E V I O U S G E O P H Y S I C A L E supporting
confidence: 91%
“…5). The agreement is similar to that reported by Hübert et al (2016) at the Newton deposit. The two datasets can also be displayed as induction arrows as in Fig.…”
Section: G E O L O G Y a N D P R E V I O U S G E O P H Y S I C A L E supporting
confidence: 91%
“…Magnetotelluric (MT) data have proven useful for 3-D studies of potential geothermal prospects in fault zones and volcanic settings in British Columbia, the Yukon and elsewhere (Unsworth et al white paper). MT has also been used effectively for mineral exploration including porphyry copper (Hubert et al 2016) and some other types of sulphide deposits ). The white paper by Risk outlines how various gas sensors could also have multiple applications ranging from monitoring volcanic activity (e.g.…”
Section: Summary Of White Papersmentioning
confidence: 99%
“…Where AMT signal levels are low, e.g., in the dead band at $ 800-3000 Hz (Garcia and Jones 2002), the controlled-source audiomagnetotelluric method (CSAMT, f = 1-10000 Hz, Zonge and Hughes 1991) is routinely applied. Consequently, MT methods have a long-standing history in the investigation of mineral deposits (Strangway et al 1973;Meju 2002;Jones 2017) with field cases reported from, for instance, copper, gold, lead, silver and zinc deposits (Kellett et al 1993;Garcia Juanatey et al 2013a, b;Hübert et al 2013;Hu et al 2013), copper, gold and iron deposits (Heinson et al 2006), copper and iron deposits (Chouteau et al 1997;Jones and Garcia 2003), copper, iron and zinc deposits (Basokur et al 1997), copper, lead and zinc deposits (Sasaki et al 1992;Bastani et al 2009), copper and nickel deposits (Lakanen 1986;Livelybrooks et al 1996;Jones et al 1997;Balch et al 1998;Stevens and McNeice 1998;Zhang et al 1998;Watts and Balch 2000;King 2007;Xiao et al 2011;Varentsov et al 2013; Le et al 2016a), copper, silver and zinc deposits (Gordon 2007), gold deposits (Jones et al 1997;Liu et al 2006;Howe et al 2014;Takam Takougang et al 2015;Hübert et al 2016;Le et al 2016b), and uranium deposits (Leppin and Goldak 2005;Tuncer et al 2006;Farquharson and Craven 2009;Goldak et al 2010;…”
Section: Mt Methods In Exploring Deep Ore Depositsmentioning
confidence: 99%